2008
DOI: 10.1158/1535-7163.mct-07-0307
|View full text |Cite
|
Sign up to set email alerts
|

A novel B-RAF inhibitor blocks interleukin-8 (IL-8) synthesis in human melanoma xenografts, revealing IL-8 as a potential pharmacodynamic biomarker

Abstract: B-RAF mutations have been identified in the majority of melanoma and a large fraction of colorectal and papillary thyroid carcinoma. Drug discovery efforts targeting mutated B-RAF have yielded several interesting molecules, and currently, three compounds are undergoing clinical evaluation. Inhibition of B-RAF in animal models leads to a slowing of tumor growth and, in some cases, tumor reduction. Described within is a novel series of diaryl imidazoles with potent, single-digit nanomolar, anti-B-RAF activity. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 34 publications
2
19
0
Order By: Relevance
“…As a consequence, in BCPAP cell lines, which express mutated BRAF V600E gene [18,19], other pathways, sustaining the high concentrations of CXCL8, are likely involved. This would be in line with the recent demonstration that high basal extracellular signal-regulated kinase 1/2 (ERK1/2) phosphorylation, which characterizes cells harboring the BRAF V600E mutation is responsible for CXCL8 secretion [20]. The above evidences support the concept that the secretion of CXCL8 by thyroid tumor cells is dependent upon different pathways which i) would be switched on by specific genetic lesions; ii) would be more or less effective in enhancing the secretion of CXCL8.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…As a consequence, in BCPAP cell lines, which express mutated BRAF V600E gene [18,19], other pathways, sustaining the high concentrations of CXCL8, are likely involved. This would be in line with the recent demonstration that high basal extracellular signal-regulated kinase 1/2 (ERK1/2) phosphorylation, which characterizes cells harboring the BRAF V600E mutation is responsible for CXCL8 secretion [20]. The above evidences support the concept that the secretion of CXCL8 by thyroid tumor cells is dependent upon different pathways which i) would be switched on by specific genetic lesions; ii) would be more or less effective in enhancing the secretion of CXCL8.…”
Section: Discussionsupporting
confidence: 82%
“…Compounds with anti-BRAF kinase activity were successfully tested for their ability to block CXCL8 synthesis in melanoma cell lines harboring the BRAFV600E mutation [20]. In addition, besides type I and Type II interferons which were previously shown to inhibit the secretion of CXCL8 [13,15], other potentially interesting molecules to be tested for their CXCL8 inhibiting effects could include PPAR-c agonists.…”
Section: Discussionmentioning
confidence: 99%
“…Its production is known to be regulated by the RET receptor (38), and the inhibitory effect observed during sunitinib exposure is likely to be due, at least partly, to the inhibition of RET phosphorylation, as shown in Western blotting and siRNA experiments. Decreased tumor secretion of IL-8 during sunitinib treatment, observed both in vitro and in vivo, has been described in other carcinomas and can be due to other mechanisms including inhibition of VEGF regulatory loops (39). Furthermore, recent results indicated that IL-8 is highly expressed in some carcinomas (40) and could mediate sunitinib resistance in renal carcinoma (41).…”
Section: Discussionmentioning
confidence: 93%
“…Interestingly, production of IL-8, which plays a role in the extravasation of melanoma cells by mediating ICAM-1 interaction with b2 integrin, was shown to be decreased following inhibition of BRAFV600E (29). Moreover, elevated plasma levels of IL-8 in mice bearing BRAFV600E melanoma xenografts were decreased by RAF inhibitor treatment (30). Our observation is consistent with these findings and, taken together, these findings suggest that reduction of IL-8 production may be important for prevention of metastasis in melanoma by RAF inhibitors and minimizing tumorigenic risk in nontarget tissues by MEK inhibitors.…”
Section: Discussionmentioning
confidence: 99%